Silicon-containing coating and preparation method thereof as well as modified nylon material as well as preparation method and application thereof

By applying a silicon-containing coating on the surface of nylon fibers, the surface polarity is improved and the low-temperature curing is achieved, the problems of difficulty in removing existing mold release fabrics and fiber breakage are solved, and the good mold release effect and efficient production of modified nylon materials are achieved.

CN119614078APending Publication Date: 2025-03-14JIANGSU AIHE COMPOSITE MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411823841.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing mold release cloth is difficult to easily remove from the surface of composite products under the premise of ensuring the demolding effect, and the high surface polarity leads to the strong oxidation resin easily reacting with the fiber cloth, resulting in the breakage and residue of the fiber cloth.

Method used

Modified nylon material modified with silicon-containing coating is used as the mold release cloth. By coating the silicon-containing coating on the surface of nylon fibers, the surface polarity is improved, and the use of low-molecular-weight polysiloxanes can achieve low temperature curing and improve the binding force between the coating and the fiber.

Benefits of technology

The mold release effect of modified nylon materials is achieved, and it is easy to remove from the surface of composite products after use, which reduces post-treatment time, improves production efficiency, and avoids the heat shrinkage of nylon fibers under high-temperature processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614078A_ABST
    Figure CN119614078A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite material forming, and particularly relates to a silicon-containing coating and a preparation method thereof as well as a modified nylon material as well as a preparation method and application thereof. Polysiloxane with small molecular weight is adopted, so that the product can be cured and formed at low temperature, energy consumption in the production process is reduced, and the thermal shrinkage phenomenon of nylon fibers in a high-temperature process is avoided. The silicon-containing coating provided by the invention not only can be cured and molded at low temperature, but also can resist higher temperature, the raw materials are easy to obtain, and the cost is controllable. According to the modified nylon material provided by the invention, the surface polarity of the nylon fiber is improved by utilizing the silicon-containing coating, the obtained modified nylon material not only has good thermal stability and no silicon migration, but also is easy to remove from the surface of a composite material product after being used, and grains of fiber cloth are reserved on the surface of the product, so that the post-treatment time of the product is shortened, and the service life of the product is prolonged. And the production efficiency of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material molding, and specifically relates to a silicon-containing coating and a preparation method thereof, as well as a modified nylon material and a preparation method and application thereof. Background Art

[0002] At present, the molding of resin-based composite materials mainly utilizes vacuum infusion process, drying process and autoclave molding process. During the implementation of these processes, release cloth is required to isolate the resin from other auxiliary materials. After the resin is cured and formed, the release cloth is removed to obtain a composite product.

[0003] According to the material, there are three types of release cloth: polyester release cloth, nylon release cloth and PTFE release cloth. Although PTFE release cloth has a good release effect, its surface is smooth, and the surface of the composite material obtained needs to be polished before the subsequent process; although polyester release cloth and nylon release cloth can leave the texture of fiber cloth on the surface of the composite material, reducing the post-processing time, it is not easy to release the mold due to the high surface polarity. If the resin content in contact is high and the oxidizing property is strong, forced peeling will easily cause the fiber cloth to break, and a large amount of residue on the resin surface is difficult to clean.

[0004] In summary, the existing demoulding cloth cannot make it easy to remove from the surface of the composite material product while ensuring the demoulding effect. Summary of the invention

[0005] The purpose of the present invention is to provide a silicon-containing coating and a preparation method thereof, as well as a modified nylon material and a preparation method and application thereof. The modified nylon material modified by the silicon-containing coating provided by the present invention has a good demoulding effect and is easy to be removed from the surface of the composite material product after use.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The invention provides a silicon-containing coating, which is prepared from the following raw materials in parts by weight: 5-20 parts of hexamethylcyclotrisiloxane, 5-20 parts of octamethylcyclotetrasiloxane, 5-15 parts of methylphenylvinylpolysiloxane, 0.5-5 parts of an anchoring agent, 0.5-5 parts of a platinum catalyst, 0.1-0.5 parts of an inhibitor and 100-500 parts of toluene; the viscosity of the methylphenylvinylpolysiloxane at 25°C is 10000-50000 mPa·s.

[0008] Preferably, the vinyl segment ratio of the methylphenylvinyl polysiloxane is 0.4%, and the phenyl segment ratio is 10-30%.

[0009] Preferably, the anchoring agent is a silane anchoring agent; the silane anchoring agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and 3-glycidyloxypropyltriethoxysilane.

[0010] Preferably, the inhibitor is a hydroxyl-containing inhibitor.

[0011] The present invention also provides a method for preparing the silicon-containing coating described in the above scheme, comprising the following steps:

[0012] Hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, methylphenylvinylpolysiloxane, an anchoring agent, an inhibitor and toluene are premixed to obtain a premixed liquid; the premixed liquid and a platinum catalyst are mixed to obtain the silicon-containing coating.

[0013] The present invention also provides a modified nylon material, comprising nylon fiber and a silicon-containing coating covering the surface of the nylon fiber; the silicon-containing coating is formed by the silicon-containing coating described in the above scheme or the silicon-containing coating obtained by the preparation method described in the above scheme.

[0014] Preferably, the weight ratio of the silicon-containing coating to the nylon fiber is 1:10-150.

[0015] The present invention also provides a method for preparing the modified nylon material described in the above scheme, comprising the following steps:

[0016] The silicon-containing coating is coated on the surface of the nylon fiber and then dried and solidified to obtain the modified nylon material.

[0017] Preferably, the curing temperature is 90 to 150° C., and the heat preservation and curing time is 30 to 120 seconds.

[0018] The present invention also provides the use of the modified nylon material described in the above scheme or the modified nylon material obtained by the preparation method described in the above scheme as a release cloth.

[0019] The present invention provides a silicon-containing coating. The silicon-containing coating provided by the present invention is used to prepare a modified nylon material, improves the surface polarity of nylon fibers, and the obtained modified nylon material not only has good thermal stability, no silicon migration, and good demoulding effect, but is also easy to remove from the surface of a composite material product after use, and leaves the texture of the fiber cloth on the surface of the product, thereby reducing the time for post-processing of the product and improving the production efficiency of the composite material.

[0020] In addition, the present invention uses polysiloxane with a relatively small molecular weight to enable the product to be cured and formed at low temperature, which not only reduces energy consumption in the production process, but also avoids the thermal shrinkage of nylon fibers under high temperature processes. The silicon-containing coating provided by the present invention can not only be cured and formed at low temperature, but also withstand higher temperatures, and the raw materials are easily available and the cost is controllable.

[0021] The present invention also provides a method for preparing the silicon-containing coating in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation and low cost.

[0022] The present invention also provides a modified nylon material. The modified nylon material provided by the present invention improves the surface polarity of nylon fiber by using silicon-containing coating, and the obtained modified nylon material not only has good thermal stability, no silicon migration, and good demoulding effect, but also is easy to remove from the surface of composite material products after use, and leaves the texture of fiber cloth on the surface of the product, which reduces the time of post-processing of the product and improves the production efficiency of the composite material.

[0023] The present invention also provides a method for preparing the modified nylon material described in the above scheme. The preparation method provided by the present invention can adjust the silicon-containing coating content of the nylon fiber by controlling the dipping time, thereby ensuring that the modified nylon material is easy to remove from the surface of the composite material product after use, and leaving the texture of the nylon fiber cloth on the surface of the product, thereby reducing the time for post-processing of the product.

[0024] The present invention also provides the use of the modified nylon material described in the above scheme or the modified nylon material obtained by the preparation method described in the above scheme as a demoulding cloth. The modified nylon material provided by the present invention has a good demoulding effect and leaves a fiber cloth texture on the surface of the product, and is suitable for use as a demoulding cloth in the field of composite material molding and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The scanning electron microscope images of nylon fiber cloth and modified nylon materials of Examples 3 and 5;

[0027] Figure 2 The water drop contact angle diagrams of nylon fiber cloth, modified nylon materials of Examples 1 and 3 to 6;

[0028] Figure 3 The photoelectron spectra of nylon fiber cloth and modified nylon materials of Examples 1, 3 and 5;

[0029] Figure 4 This is a diagram of the actual application of the autoclave of the modified nylon material of Examples 1 and 3 to 6. DETAILED DESCRIPTION

[0030] The invention provides a silicon-containing coating, which is prepared from the following raw materials in parts by weight: 5 to 20 parts of hexamethylcyclotrisiloxane, 5 to 20 parts of octamethylcyclotetrasiloxane, 5 to 15 parts of methylphenylvinylpolysiloxane, 0.5 to 5 parts of an anchoring agent, 0.5 to 5 parts of a platinum catalyst, 0.1 to 0.5 parts of an inhibitor and 100 to 500 parts of toluene.

[0031] The raw materials of the silicon-containing coating provided by the present invention include 5 to 20 parts of hexamethylcyclotrisiloxane (D3), specifically 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts. The present invention uses hexamethylcyclotrisiloxane as one of the main raw materials for the reaction.

[0032] The raw materials of the silicon-containing coating provided by the present invention include 5 to 20 parts of octamethylcyclotetrasiloxane (D4), specifically 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts. The present invention uses octamethylcyclotetrasiloxane as one of the main raw materials for the reaction.

[0033] The raw materials of the silicon-containing coating provided by the present invention include 5 to 15 parts of methylphenyl vinyl polysiloxane, specifically 7 parts, 9 parts, 11 parts or 13 parts. The present invention uses methylphenyl vinyl polysiloxane as one of the main raw materials for the reaction.

[0034] In the present invention, the viscosity of the methylphenyl vinyl polysiloxane at 25°C is 10,000 to 50,000 mPa·s, specifically 15,000 mPa·s, 20,000 mPa·s, 25,000 mPa·s, 30,000 mPa·s, 35,000 mPa·s, 40,000 mPa·s or 45,000 mPa·s, the vinyl segment ratio is preferably 0.4%, and the phenyl segment ratio is preferably 10 to 30%, specifically 15%, 20% or 25%.

[0035] The raw materials of the silicon-containing coating provided by the present invention include 0.5 to 5 parts of an anchoring agent, specifically 0.7 parts, 0.9 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts. The present invention improves the adhesion between the coating formed by the silicon-containing coating and the nylon fiber cloth through the adhesion promoter.

[0036] In the present invention, the anchoring agent is preferably a silane anchoring agent; the silane anchoring agent preferably includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and 3-glycidyloxypropyltriethoxysilane.

[0037] The raw materials of the silicon-containing coating provided by the present invention include 0.5 to 5 parts of a platinum catalyst, specifically 0.7 parts, 0.9 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.8 parts.

[0038] In the present invention, the platinum catalyst is preferably a platinum / olefin siloxane coordination compound; the effective content of the platinum catalyst is preferably 10000 ppm.

[0039] The raw materials of the silicon-containing coating provided by the present invention include 0.1 to 0.5 parts of an inhibitor, specifically 0.2 parts, 0.3 parts or 0.4 parts. The inhibitor is mainly used to slow down the reaction speed and prevent implosion.

[0040] In the present invention, the inhibitor is preferably a hydroxyl-containing inhibitor; the hydroxyl-containing inhibitor is preferably an unsaturated alcohol; the unsaturated alcohol is preferably 2-methyl-3-butyn-2-ol.

[0041] The raw material of the silicon-containing coating provided by the present invention includes 100 to 500 parts of toluene, specifically 120 parts, 150 parts, 170 parts, 200 parts, 240 parts, 270 parts, 300 parts, 350 parts, 400 parts or 450 parts. The present invention uses toluene as a solvent to play a diluting role, thereby adjusting the coating amount of the silicon-containing coating.

[0042] The present invention also provides a method for preparing the silicon-containing coating described in the above scheme, comprising the following steps:

[0043] Premixing hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, methylphenylvinylpolysiloxane, an anchoring agent, an inhibitor and toluene to obtain a premixed solution;

[0044] The premixed liquid and the platinum catalyst are mixed to obtain the silicon-containing coating.

[0045] In the present invention, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, methylphenylvinylpolysiloxane, an anchoring agent, an inhibitor and toluene are premixed to obtain a premixed liquid. In the present invention, the premixing is preferably stirred and mixed; the premixing time is preferably 10 to 30 minutes, specifically 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0046] After obtaining the premixed liquid, the present invention mixes the premixed liquid with a platinum catalyst to obtain the silicon-containing coating. In the present invention, the mixing is preferably stirring and mixing; and the mixing time is preferably 5 minutes.

[0047] The present invention also provides a modified nylon material, comprising nylon fiber and a silicon-containing coating covering the surface of the nylon fiber; the silicon-containing coating is formed by the silicon-containing coating described in the above scheme or the silicon-containing coating obtained by the preparation method described in the above scheme.

[0048] The modified nylon material provided by the present invention comprises nylon fibers; the warp and weft density of the nylon fibers is preferably 158*158 strands / dm, 315*244 strands / dm or 409*343 strands / dm.

[0049] The modified nylon material provided by the present invention comprises a silicon-containing coating covered on the surface of the nylon fiber; the gram-to-weight ratio of the silicon-containing coating to the nylon fiber is preferably 1:10-150, specifically 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140 or 1:150.

[0050] The present invention also provides a method for preparing the modified nylon material described in the above scheme, comprising the following steps:

[0051] The silicon-containing coating is coated on the surface of the nylon fiber and then dried and solidified to obtain the modified nylon material.

[0052] In the present invention, the coating is preferably dip-coating; the number of dip-coating is preferably 1 time; the dipping time is preferably 5 to 15 seconds, specifically 7 seconds, 9 seconds, 11 seconds or 13 seconds.

[0053] In the present invention, the drying is preferably oven drying; the drying temperature is preferably 50-70°C, specifically 55°C, 60°C or 65°C, and the heat preservation and drying time is preferably 1-3 minutes, specifically 2 minutes.

[0054] In the present invention, the curing temperature is preferably 90 to 150°C, specifically 100°C, 110°C, 120°C, 130°C or 140°C, and the heat preservation curing time is preferably 30 to 120s, specifically 40s, 60s, 80s or 100s. In the curing process of the present invention, under the action of a platinum catalyst, diene bonds, silicon-hydrogen bonds or hydroxyl groups in the organosiloxane (hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane and methylphenylvinylpolysiloxane) undergo addition or condensation reactions, cross-linking to form a 3D network structure, and the binding force between the coating and the nylon fiber is increased by an anchoring agent, thereby achieving a modified nylon material with a demolding effect.

[0055] In the present invention, the curing preferably further includes cooling the product and then rolling it up.

[0056] The present invention also provides the use of the modified nylon material described in the above scheme or the modified nylon material obtained by the preparation method described in the above scheme as a release cloth.

[0057] The modified nylon material provided by the invention has good demoulding effect and leaves fiber cloth texture on the surface of the product, so it is suitable for use as demoulding cloth and is used in the fields of composite material molding and the like.

[0058] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0059] Example 1

[0060] 10 parts of hexamethylcyclotrisiloxane (D3), 10 parts of octamethylcyclotetrasiloxane (D4), 5 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 10%), 0.5 parts of anchoring agent (γ-aminopropyltriethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol) and 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0061] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 158*158 strands / dm, immerse the nylon fiber cloth in the glue tank for 5 seconds, transfer it to a 60°C drying section oven for drying for 1 minute, then transfer it to a 120°C curing section oven for curing for 60 seconds, and roll it up to obtain a modified nylon material.

[0062] Example 2

[0063] 5 parts of hexamethylcyclotrisiloxane (D3), 5 parts of octamethylcyclotetrasiloxane (D4), 15 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 20%), 0.5 parts of anchoring agent (γ-aminopropyltriethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol) and 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000 ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0064] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 409*343 strands / dm, immerse the nylon fiber cloth in the glue tank for 5 seconds, transfer it to a 60°C drying section oven for drying for 1 minute, then transfer it to a 120°C curing section oven for curing for 60 seconds, and roll it up to obtain a modified nylon material.

[0065] Example 3

[0066] 5 parts of hexamethylcyclotrisiloxane (D3), 5 parts of octamethylcyclotetrasiloxane (D4), 15 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 20%), 0.5 parts of anchoring agent (γ-aminopropyltriethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol) and 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000 ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0067] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 409*343 strands / dm, immerse the nylon fiber cloth in the glue tank for 5 seconds, transfer it to a drying section oven at 60°C for drying for 1 minute, then transfer it to a curing section oven at 150°C for curing for 30 seconds, and roll it up to obtain a modified nylon material.

[0068] Example 4

[0069] 10 parts of hexamethylcyclotrisiloxane (D3), 8 parts of octamethylcyclotetrasiloxane (D4), 7 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 10%), 0.5 parts of anchoring agent (γ-glycidyloxypropyltrimethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol) and 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000 ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0070] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 409*343 strands / dm, immerse the nylon fiber cloth in the glue tank for 10 seconds, transfer it to a 60°C drying section oven for drying for 2 minutes, then transfer it to a 120°C curing section oven for curing for 60 seconds, and roll it up to obtain a modified nylon material.

[0071] Example 5

[0072] 10 parts of hexamethylcyclotrisiloxane (D3), 8 parts of octamethylcyclotetrasiloxane (D4), 7 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 10%), 0.5 parts of anchoring agent (γ-glycidyloxypropyltrimethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol), 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000 ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0073] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 409*343 strands / dm, immerse the nylon fiber cloth in the glue tank for 15 seconds, transfer it to a drying section oven at 60°C for drying for 3 minutes, then transfer it to a curing section oven at 120°C for curing for 60 seconds, and roll it up to obtain a modified nylon material.

[0074] Example 6

[0075] 10 parts of hexamethylcyclotrisiloxane (D3), 8 parts of octamethylcyclotetrasiloxane (D4), 7 parts of methylphenylvinylpolysiloxane (vinyl segment ratio is 0.4%, phenyl segment ratio is 10%), 0.5 parts of anchoring agent (γ-glycidyloxypropyltrimethoxysilane), 0.1 parts of inhibitor (2-methyl-3-butyn-2-ol), 300 parts of toluene are added into a container, stirred evenly for 15 minutes, and then 1.2 parts of platinum catalyst (platinum / olefin siloxane coordination compound, effective content is 10000 ppm) are added and stirred for 5 minutes to obtain a silicon-containing coating.

[0076] Pour the silicon-containing coating into the glue tank, select a nylon fiber cloth with a warp and weft density of 409*343 strands / dm, immerse the nylon fiber cloth in the glue tank for 10 seconds, transfer it to a 60°C drying section oven for drying for 2 minutes, then transfer it to a 90°C curing section oven for curing for 120 seconds, and roll it up to obtain a modified nylon material.

[0077] Table 1 Formulations and process parameters of Examples 1 to 6

[0078]

[0079]

[0080] Test Example 1

[0081] The modified nylon materials prepared in Examples 1 to 6 were tested for coating amount, release force, residual rate and 180° peeling force of glass fiber epoxy resin prepreg. The release force test method was as follows: tesa TM The 7475 tape is attached to the release surface of the modified nylon material to be tested, and after being rolled back and forth three times with a 2kg pressure roller, it is cut to obtain a 25mm×130mm specimen; the specimen is placed at room temperature for 20 minutes and then attached to a steel plate with adhesive. The 7475 tape is peeled off at an angle of 180° and a peeling speed of 300mm / min using a tensile testing machine. The reading of the tensile testing machine is the 20min release force.

[0082] The residual rate test method is: Standard tape NITTO TM31B is attached to the release surface of the modified nylon material to be tested, and rolled back and forth three times with a 2kg pressure roller, and cut to obtain a 25mm*300mm specification specimen, and the specimen is placed horizontally between two glass plates. The glass plate is placed at 70℃, 50%RH, and 2kg pressure block pressure for 20 hours; then the specimen is taken out after cooling at room temperature for 4 hours. The 31B standard tape on the specimen is slowly peeled off from the release film and then attached to the steel plate, and a 2kg electric pressure roller is used to roll back and forth twice at a speed of 300mm / min under its own weight. After placing it for 20 minutes, the tape is peeled off at a speed of 300mm / min on the tensile testing machine, and the average peeling force of the tensile testing machine reading is recorded as L1.

[0083] A new 31B standard tape (the same roll as the tape used for the sample strip) is directly attached to the steel plate, and rolled back and forth twice at a speed of 300 mm / min under its own weight, and left for 20 minutes. The tape is peeled off at a speed of 300 mm / min on the tensile testing machine, and the average peeling force of the tensile testing machine reading is recorded as L0. The residual rate is calculated as: L1 / L0×100%. The higher the residual rate, the better the performance of the modified nylon material, and the less effect it has on the viscosity of the sticky material attached to its surface.

[0084] The 180° peel test method refers to GB / T 2792-2014, and the results are shown in Table 2.

[0085] Table 2 Test results of modified nylon materials properties of Examples 1 to 6

[0086]

[0087]

[0088] It can be seen from Table 1 and Table 2 that although the molecular weight of methylphenylvinyl polysiloxane is relatively large, which is helpful for the temperature resistance of silicone, the reaction activity is relatively low and a relatively high temperature is required for curing; and due to the presence of internal active amide groups, nylon fiber cloth will cause undesirable phenomena such as yellowing or shrinkage of the fiber cloth if it stays in a high temperature environment for too long, so a high proportion of methylphenylvinyl polysiloxane is not suitable; as the dipping time increases, the surface coating amount of the nylon fiber cloth also increases, and it is also easier to peel off from the surface of the resin prepreg; since the present invention adopts low molecular weight polysiloxane, the steric hindrance effect is small, the reaction activity is high, and the reaction can be carried out at low temperature. The product obtained by reacting at 90°C for 2 minutes has basically the same effect as the product obtained by reacting at 120°C for 1 minute, which reduces energy consumption on the one hand and protects the nylon fiber cloth on the other hand.

[0089] Test Example 2

[0090] The nylon fiber cloth and the modified nylon materials of Example 3 and Example 5 were analyzed by scanning electron microscope. The results are as follows: Figure 1 As shown. Figure 1 It can be clearly seen that the structure of the nylon fiber cloth is relatively loose, and the gaps between the fibers are relatively large. After the silicon-containing coating is applied to the nylon fiber, the fiber surface has obvious changes, as shown in the scanning electron microscope image of Example 3. As the coating amount increases, the degree of coating covering the fiber is gradually increasing. The coating amount of Example 5 is 6.6 g / m 2 The coating amount of Example 3 is 1.5 g / m 2 .

[0091] The water drop contact angle test was performed on the nylon fiber cloth, the modified nylon materials of Example 1 and Examples 3 to 6. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the nylon fiber cloth is in a wetted state due to the absence of any coating on its surface, and the silicon-containing coating content of Example 5 is the highest, so its water drop contact angle is the largest, followed by Example 4 and Example 1. As the content of the silicon-containing coating decreases, the water drop contact angle also decreases. The water drop contact angle of Example 2 is small due to the high content of high molecular weight silicone, low low temperature reaction activity, and incomplete reaction. High molecular weight silicone is easy to cause shrinkage of the nylon fiber cloth when reacting at high temperature, so the content of high molecular weight silicone should not be too high.

[0092] Photoelectron spectroscopy analysis was performed on the nylon fiber cloth, the modified nylon materials of Example 1, Example 3 and Example 5, and the results were as follows: Figure 3 As shown. Figure 3 It can be seen that with the gradual increase in the weight of the silicon-containing coating, the content of Si element also increases significantly, and it has a good adhesion effect on the surface of nylon fiber.

[0093] The modified nylon materials of Example 1 and Examples 3 to 6 were tested in an autoclave. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that when there is no silicon-containing coating or the silicon-containing coating content is low, it is difficult to peel off from the prepreg surface after use. As the silicon-containing coating content increases, the surface release property is significantly improved, and the nylon fiber cloth can be completely peeled off from the prepreg surface, thereby playing the role of the release cloth. In Example 3, due to the high production temperature, the nylon fiber cloth is deformed and the effect is not good after use. From the comparison of the use of Example 5 and Example 6, the low reaction temperature can make the silicon-containing coating adhere to the nylon fiber, which has the same effect as the high-temperature reaction, which can not only reduce energy consumption, but also reduce the impact of high temperature on the nylon fiber cloth.

[0094] It can be seen from the above embodiments that the modified nylon material modified with the silicon-containing coating provided by the present invention has good demoulding effect, good temperature resistance, and leaves the texture of fiber cloth on the surface of the product.

[0095] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A silicon-containing coating, characterized in that: The invention is prepared from the following raw materials in parts by weight: 5 to 20 parts of hexamethylcyclotrisiloxane, 5 to 20 parts of octamethylcyclotetrasiloxane, 5 to 15 parts of methylphenylvinylpolysiloxane, 0.5 to 5 parts of an anchoring agent, 0.5 to 5 parts of a platinum catalyst, 0.1 to 0.5 parts of an inhibitor and 100 to 500 parts of toluene; the viscosity of the methylphenylvinylpolysiloxane at 25° C. is 10,000 to 50,000 mPa·s.

2. The silicon-containing coating according to claim 1, characterized in that The vinyl segment ratio of the methylphenylvinyl polysiloxane is 0.4%, and the phenyl segment ratio is 10-30%.

3. The silicon-containing coating according to claim 1 or 2, characterized in that: The anchoring agent is a silane anchoring agent; the silane anchoring agent includes one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and 3-glycidyloxypropyltriethoxysilane.

4. The silicon-containing coating according to claim 1 or 2, characterized in that: The inhibitor is a hydroxyl-containing inhibitor.

5. The method for preparing the silicon-containing coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: Premixing hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, methylphenylvinylpolysiloxane, an anchoring agent, an inhibitor and toluene to obtain a premixed solution; The premixed liquid and the platinum catalyst are mixed to obtain the silicon-containing coating.

6. A modified nylon material, characterized in that: The invention comprises nylon fiber and a silicon-containing coating covering the surface of the nylon fiber; the silicon-containing coating is formed by the silicon-containing coating according to any one of claims 1 to 4 or the silicon-containing coating obtained by the preparation method according to claim 5.

7. The modified nylon material according to claim 6, characterized in that: The weight ratio of the silicon-containing coating to the nylon fiber is 1:10-150.

8. The method for preparing the modified nylon material according to any one of claims 6 to 7, characterized in that: The following steps are involved: The silicon-containing coating is coated on the surface of the nylon fiber and then dried and solidified to obtain the modified nylon material.

9. The preparation method according to claim 8, characterized in that: The curing temperature is 90-150° C., and the heat preservation curing time is 30-120 seconds.

10. Use of the modified nylon material according to any one of claims 6 to 7 or the modified nylon material obtained by the preparation method according to any one of claims 8 to 9 as a release cloth.

Citation Information

Patent Citations

  • Linear organosilicon acrylate, preparation method and applications thereof

    CN108203511A

  • High-temperature-resistant low-transfer organosilicone release agent and preparation method thereof

    CN109880523A

  • Solvent-free organic silicon release agent with ultralow release force and preparation method thereof

    CN114058290A

  • Strippable cloth for composite material forming and preparation method and application thereof

    CN117779460A